2022
DOI: 10.3390/diagnostics12030754
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mean Corneal Power of Annular Rings and Zones Using Swept-Source Optical Coherence Tomography

Abstract: This study aims to investigate differences in the mean corneal power of annular zones (corneal power measured over the inner annular zone of difference diameters) and rings (corneal power measured over a ring of different diameters) centered on the corneal apex using the swept-source optical coherence tomography technique. The mean anterior axial curvature (AAC), posterior axial curvature (PAC), and total corneal power (TCP) centered on the corneal apex with the annular rings (0–2 mm, 2–4 mm, 4–6 mm, and 6–8 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It has been shown that another method of measuring corneal power is by using optical coherence tomography (OCT). 30 OCT has shown to be comparable to conventional keratometry 31 and used for IOL calculations. 32 Wang et al compared the measurements obtained by OCT to measurements obtained with the Pentacam in healthy, unoperated eyes.…”
Section: Discussionmentioning
confidence: 94%
“…It has been shown that another method of measuring corneal power is by using optical coherence tomography (OCT). 30 OCT has shown to be comparable to conventional keratometry 31 and used for IOL calculations. 32 Wang et al compared the measurements obtained by OCT to measurements obtained with the Pentacam in healthy, unoperated eyes.…”
Section: Discussionmentioning
confidence: 94%
“…[6,22] ACD was measured from the corneal endothelium to the surface of the anterior lens, [23] and WTW distance is the horizontal distance between the borders of the corneal limbus. [24]…”
Section: Phakic Iols and Calculationmentioning
confidence: 99%
“… Semifluorinated Alkanes-(SFAs) SFAs were introduced in the early 2000s as a novel family of chemicals with excellent characteristics for application in vitreoretinal surgery [ 99 ]. They have an index of refraction of 1.3, which is similar to the aqueous humor (1.336) [ 158 , 159 ], they are soluble in PFCL, hydrocarbons, SiOs and contain perfluorocarbon and hydrocarbon side chains. SFAs have a specific gravity of 1.35 g/mL, are inert, and are heavier than the aqueous humor, which is the main characteristic for which they were combined with SiO [ 99 , 160 ].…”
Section: Classification Of the Vitreous Substitutes: General Principl...mentioning
confidence: 99%